Perspectives for export-oriented industrial policy strategies for selected African countries: Case studies Côte d'Ivoire, Ghana and Tunisia - Jan Grumiller; Werner G. Raza; Cornelia Staritz; Hannes Grohs; Christoph Arndt (Austrian Foundation for Development Research (ÖFSE), 2018)
The European Union (EU) has recently concluded or is currently in the process of negotiating a number of bilateral free trade agreements with both industrialized countries, e.g. Canada and Japan, and developing as well as emerging economies. Negotiations with the latter group include inter alia the Mercosur countries, Vietnam, as well as the African countries of the African, Caribbean and Pacific (ACP) group and Tunisia. Negotiations on the EU-Tunisia Deep and Comprehensive Free Trade Agreement (DCFTA) were launched in 2015 and are still ongoing. Trade agreements between advanced and developing countries like those negotiated by the European Union and the ACP countries as well as with Tunisia, respectively, pose both opportunities and threats to the partner countries involved. While results from model-based economic impact assessments typically indicate that the macroeconomic effects of such agreements tend to be small, the long-term effects depend on the structural change triggered by the agreements. It is a well-known contention in the development economics literature that the marked differences in economic capacities and capabilities between advanced and developing economies pose particular problems that need to be dealt with, if longer-term impediments to late economic development are to be avoided. Thus, in this report, the focus is directed towards discussing the challenges of productive development as well as of export promotion in selected EU partner countries and export sectors in the context of trade liberalisation. To this end, four export sectors in three African countries are analysed, namely (i) the cocoa and mango sectors in Côte d'Ivoire and Ghana, and (ii) the olive oil and the textile and apparel sectors in Tunisia. With the exception of the mango sector, the other sectors - cocoa, olive oil and textile and apparel - are well-established sectors in the respective countries. Attempts to functionally upgrade into processing for the agriculture-based cocoa and olive oil sectors are however recent, while important consolidation processes have been under way in the context of increased global competition and political instability in the context of the Arab Spring in the textile and apparel sector in Tunisia. Mango exports have only recently become a thriving export sector in Côte d'Ivoire and Ghana and have profited from strong demand growth in advanced and increasingly also emerging countries. All sector case studies are located in African countries, which figure among the prioritized partner countries for EU development cooperation. For each scrutinized sector, key policy recommendations for upgrading and diversification into higher value-added products are proposed.
Additional information: Final report, 12 July 2018
Keywords: 330